A diagnostic model of private control and collective control in buyer-supplier relationships - Liu, Y.; Luo, Yadong; Huang, Y.; Yang, Q. (Elsevier, 2017)
© 2016.This study examines the control-based governance in buyer-supplier relationships. Building on boundary spanning theory and governance literature, we propose an integrated model that consists of exchange parties' private control (aimed at individual gains) and collective control (aimed at joint gains) in boundary spanning activities, along with their structural antecedents and relationship consequences in interorganizational governance. Using data collected from manufacturer-distributor dyads, we demonstrate that a buyer-supplier relationship characterized by a high degree of distributive justice and low degrees of goal difference and power asymmetry promotes exchange parties' collective control while inhibiting private control in boundary spanning conduct. The impact of private and collective controls on dyadic relationship performance is further mediated through governance costs and returns. Specifically, private control results in conflict and transaction costs that undermine dyadic relationship performance, whereas collective control leads to solidarity and reciprocity that sustain dyadic relationship performance. Recognizing and distinguishing between private control and collective control is essential to managing boundary-spanning behavior in buyer-supplier relationships and to solidifying relationship performance in supply chain and channel management.